Peningkatan Keterampilan Menulis Puisi dengan Metode Pembelajaran Outdoor pada Siswa Kelas VII F SMP N 1 Teras - Fradita, Tia Erlin; , Dra. Main Sufanti, M.Hum (2016)
The study entitled improved skills of writing poetry with outdoor learning method in class VIIF grade students of SMP N 1 Teras Boyolali. The purpose of this classroom action research is to increase the interest and skills of writing poems at class VIIF grade students of SMP N 1 Teras Boyolali by applying methods of outdoor learning. This research is a classroom action research conducted in two cycles namely research subjects in class VIIF SMP N 1 terrace consisting of 32 students. The collected data is data skills upgrading interests and skills to write the poetry. Data collection methods used in the form of observation, interviews, documentation and oral tests for observing lessons with outdoor learning methods and assess the actions of the teacher when applying methods of outdoor learning. Data analysis with comparative descriptive analysis by comparing the results of observation with indicators of achievement of each cycle, from pre-cycle conditions, there are the first cycle and the second cycle. results of research interests and skills to write poetry at VIIF grade students of SMP N 1 Teras Boyolali by applying methods of outdoor learning has increased, it can be seen from the results of interest in writing poetry of the class before the class action or pre-cycle of the first cycle of 73.13 51.52 and the second cycle of 83.39. As for the indicators of interest scores in writing poetry is; (1) a sense of excitement, (2) interest, (3) concern, and (4) the involvement of learners. While for the skill of writing poetry before action or pre-cycle of 56.52, the first cycle of the second cycle of 73.13 and 83.39. As for the indicators of poetry writing skills (1) diction, (2) imagine, (3) the content, (4) figure of speech, (5) themes, (6) rhyme, (7) the mandate. The conclusions of this study is that outdoor learning method can improve writing skills poetry in class VIIF grade students of SMP N 1 Teras Boyolali. Keywords: skills, poetry, outdoor